Adolescent-Onset Epilepsy: Clinical Features and Predictive Factors for First-Year Seizure Freedom - Kim, Jon Soo; Woo, Hyewon; Lee, Jae Hee; Kim, Won Seop (Neuropediatrics, 2024)
Background Teenagers with epilepsy require special attention to ensure a successful treatment journey. Our objective was to delineate the clinical characteristics of adolescent-onset epilepsy (AOE) and investigate the predictive factors influencing first-year seizure freedom.Methods We retrospectively analyzed the medical records of patients whose first seizure occurred between the ages of 10 and 19 years and who received antiseizure medication (ASM) treatment for at least 12 months.Results A total of 67 patients were included, with an average age of 13.5 ± 2.3 years at the onset of their first seizure. The average follow-up period was 45.2 ± 16.9 months, and comorbid conditions were present in 23 patients (34.3%). The majority of the patient population (83.6%) was affected by generalized epilepsy. The most common epilepsy syndrome was epilepsy with generalized tonic-clonic seizures alone at 70.1% (juvenile myoclonic epilepsy 11.9%, juvenile absence epilepsy 1.5%). Regarding ASM treatment, 31 patients (46.3%) received monotherapy, and 28 (41.8%) received dual therapy. Five patients (7.5%) encountered issues related to medication adherence. First-year seizure freedom was observed in 42 patients (62.7%). In multivariate analysis, a negative family history of epilepsy (odds ratio 12.1, 95% confidence interval 1.27–115.44, p = 0.030) was identified as a strong predictive factor of first-year seizure freedom, along with ASM monotherapy (odds ratio 3.99, 95% confidence interval 1.05–15.21, p = 0.043).Conclusion These findings suggest that AOE typically exhibits effective control of seizures. A negative family history of epilepsy and ASM monotherapy emerges as robust predictor of achieving favorable outcomes within the early stage of treatment.
Keywords: adolescent; seizures; epilepsy